Method for analyzing and evaluating degradation resistance of plastic based on linear extrapolation of aerobic biological decomposition test result under controlled composting condition
By conducting aerobic biodecomposition test under controlled composting conditions and analyzing the biodecomposition rate of plastics by linear extrapolation method, the problem of difficult to quickly and accurately evaluate the hydrolysis resistance of plastics in the prior art is solved, and efficient and simple Test method improves the repetition and accuracy of the test.
Patent Information
- Application Number
- CN202411479045.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The prior art is difficult to quickly and accurately evaluate the hydrolysis resistance or hydrolysis resistance of plastics, and often requires a large number of parallel sample tests, with poor repeatability and cannot sensitively reflect the initial or surface degradation behavior of plastics.
By conducting aerobic biodecomposition tests under controlled composting conditions, the biodecomposition rate of plastics was analyzed, and the critical point of the transition from chemical degradation to biodegradation was determined by linear extrapolation method, and the hydrolysis resistance of plastics was described in quantified.
It achieves simple and efficient evaluation of the hydrolysis resistance of plastics, reduces the number of samples, improves the repetition and accuracy of the test, and can sensitively reflect the initial degradation behavior of plastics.
Smart Images

Figure BDA0005097107800000031 
Figure BDA0005097107800000037 
Figure BDA0005097107800000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material analysis, and in particular relates to a method for evaluating the anti-degradation performance of plastics, and also relates to a system, equipment and a medium thereof adopting the method. Background Art
[0002] The invention and use of plastics have greatly facilitated people's lives, but at the same time they have also caused serious environmental pollution. Biodegradable polymer materials represented by polylactic acid and polybutylene adipate terephthalate are committed to solving the problem of plastic / microplastic pollution. In addition, in the field of engineering, high-performance polymer materials represented by polyamide are also increasingly widely used. However, most of the above materials are hydrolyzable, that is, they have the necessary conditions for hydrolysis. For example, the ester bond (-COO-) in polyester materials and the amide bond (-CO-NH-) in polyamide materials can undergo hydrolysis in the presence of water and catalysts, resulting in a significant decrease in the molecular weight of the polymer and rapid deterioration of the material properties. Therefore, scientifically and reliably characterizing and evaluating the hydrolysis resistance or hydrolysis resistance of plastics is an important means to ensure the large-scale promotion and application of such plastics, and is of great significance.
[0003] At present, some characterization and analysis techniques have been developed to evaluate the properties related to plastic degradation. For example, visual observation, weight loss weighing, mechanical property evaluation, molecular weight evaluation, melt index evaluation, etc. can reflect the degree of degradation of the tested plastic at a certain moment to a certain extent, but each has its own defects. For example, the visual observation method requires a high time cost to make the sample achieve visible degradation, and the results are somewhat subjective; the weight loss weighing method cannot measure the degradation fluctuations in the short term, and cannot reflect the impact of rapid changes in process parameters on the degradation rate of plastics; the mechanical property evaluation method cannot be used to test broken plastics during the degradation process; the molecular weight evaluation method requires the use of advanced chromatographic instruments to separate and characterize the polymer chains of different molecular weights during the degradation process, and has high requirements for testing instruments and testers; the melt index evaluation method measures the comprehensive properties of degraded and undegraded polymer mixtures, especially in the early stage of degradation, the impact of a small amount of degraded polymers on the overall melt index may be lower than the accidental error of this method, and accurate results cannot be obtained. It is known in the art that the test and evaluation methods known in the prior art are usually extra destructive to the samples being tested, and therefore require a large number of parallel sample tests to obtain the trend of changes in relevant performance over time, and have relatively high requirements for the samples, personnel, equipment, environment, etc. tested, and the test repeatability is also poor. In addition, the above methods are usually insensitive to the small amount of degradation behavior of plastics in the early stage or on the surface of the material, and cannot sensitively and accurately reflect the anti-degradation performance (such as hydrolysis resistance or hydrolysis resistance) of the plastic test material.
[0004] Therefore, there is still a need to develop characterization analysis methods for evaluating the degradation performance of plastics to achieve a simple test analysis process without relying on a large number of parallel sample tests. More ideally, the method can sensitively and accurately reflect the hydrolysis resistance or hydrolysis resistance of plastics.
[0005] The inventors unexpectedly discovered that by analyzing and characterizing the results of aerobic biodegradation tests of plastics known in the art under controlled composting conditions, the critical transition time point (i.e., critical point) of the early, middle or early stages of the test from a chemical degradation process involving no microorganisms (i.e., hysteresis stage) to a biochemical process involving microorganisms (i.e., biodegradation stage) can be obtained. The numerical value of the critical point reflects the precise information on the length of time or speed required for the plastic to degrade to a molecular weight level that can be digested and absorbed by microorganisms under aerobic controlled composting conditions, thereby solving the above-mentioned deficiencies of the prior art and further serving as an indicator parameter for evaluating the hydrolysis resistance or hydrolysis resistance of plastics. Summary of the invention
[0006] An object of the present invention is to overcome at least one shortcoming of the prior art, and in particular to provide a method for evaluating the anti-degradation performance of plastics. The method is based on linear extrapolation to analyze the results of aerobic biodegradation tests of plastics under controlled composting conditions. The method can quantitatively describe the differences and critical transition points between the chemical degradation (mainly hydrolysis reaction) involving non-microorganisms and the biodegradation behaviors involving microorganisms in the early, middle or early stages of the aerobic biodegradation test, thereby being used to evaluate the advantages and disadvantages of the anti-hydrolysis or hydrolysis resistance of plastics (especially hydrolyzable plastics such as polyesters and polyamides) of different types, processes, formulas and batches.
[0007] According to a first aspect of the present invention, a method for analyzing and evaluating the anti-degradation performance of plastics based on the linear extrapolation method of aerobic biodegradation test results under controlled composting conditions is provided, characterized in that the method comprises the following steps:
[0008] (1) conducting aerobic biodegradation tests on plastics under controlled composting conditions and obtaining the results of said tests,
[0009] Wherein, the plastic is i The biodegradability (%) of |i=1,2,3,...,n} is recorded as
[0010] (2) performing data processing and graphing of the biodegradability of the plastic,
[0011] Among them, the logarithmic operation is used to convert the obtained value in step (1) into Convert to And plot y 1The scatter plot relative to t is denoted as P 1 ={(y 1i ,t i )|i=1,2,3,...,n}, where {a 1 >0∩a 1 ≠1|a 1 ∈R}, that is, a 1 >0 and not equal to 1, and Right now
[0012] (3) For the scatter plot P in step (2) 1 Perform linear fitting and linear extrapolation.
[0013] Among them, the scatter plot P 1 Divide the data into at least two segments that are basically linearly related and contain as many continuous data points as possible, perform linear fitting on the data points of each segment, and record the data point of the segment with the largest slope of the linear fitting as P 1A , and its linear fitting equation is expressed as Equation 1:
[0014] Y 1A =k 1A t+c 1A Equation 1
[0015] P 1A The data point of the segment with the smallest slope of the linear fit on the left is recorded as P 1B , and its linear fitting equation is expressed as Equation 2:
[0016] Y 1B =k 1B t+c 1B Equation 2
[0017] where k 1A >0, and k 1A >k 1B ,
[0018] And wherein, the straight lines described by equation 1 and equation 2 are linearly extrapolated to obtain the intersection point, and the time t corresponding to the intersection point is obtained. c1 ;and
[0019] (4) Output analysis results,
[0020] The result includes the parameter t obtained in step (3) c1 , optionally also including k 1A and / or k 1B .
[0021] According to a second aspect of the present invention, there is provided a method for analyzing and evaluating the anti-degradation performance of plastics based on the linear extrapolation method of the aerobic biodegradation test results under controlled composting conditions, characterized in that the method comprises the following steps:
[0022] (1) conducting aerobic biodegradation tests on plastics under controlled composting conditions and obtaining the results of said tests,
[0023] Wherein, the plastic is i The biodegradability (%) of |i=1,2,3,...,n} is recorded as
[0024] (2) performing data processing and graphing of the biodegradability of the plastic,
[0025] Among them, the logarithmic operation is used to convert the obtained value in step (1) into Convert to And convert time t into And plot y 2 Relative to x 1 The scatter plot is denoted as P 2 ={(y 2i ,x 1i )|i=1,2,3,...,n}, where {a 2 >0∩a 2 ≠1|a 2 ∈R}, that is, a 2 >0 and not equal to 1, and Right now
[0026] (3) For the scatter plot P in step (2) 2 Perform linear fitting and linear extrapolation.
[0027] Among them, the scatter plot P 2 Divide the data into at least two segments that are basically linearly related and contain as many continuous data points as possible, perform linear fitting on the data points of each segment, and record the data point of the segment with the largest slope of the linear fitting as P 2A , and its linear fitting equation is expressed as Equation 3:
[0028] Y 2A =k 2A x 1 +c 2A Equation 3
[0029] P 2A The data point of the segment with the smallest slope of the linear fit on the left is recorded as P 2B, and its linear fitting equation is expressed as Equation 4:
[0030] Y 2B =k 2B x 1 +c 2B Equation 4
[0031] where k 2A >0, and k 2A >k 2B ,
[0032] And wherein, the straight lines described by equation 3 and equation 4 are linearly extrapolated to obtain the intersection point, and the x corresponding to the intersection point is obtained. c2 , and by the equation Obtain the time t corresponding to the intersection point c2 ;and
[0033] (4) Output analysis results,
[0034] The result includes the parameter t obtained in step (3) c2 , optionally also including k 2A and / or k 2B .
[0035] According to a third aspect of the present invention, there is provided a method for analyzing and evaluating the anti-degradation performance of plastics based on the linear extrapolation method of the aerobic biodegradation test results under controlled composting conditions, characterized in that the method comprises the following steps:
[0036] (1) conducting aerobic biodegradation tests on plastics under controlled composting conditions and obtaining the results of said tests,
[0037] Wherein, the plastic and the reference material are i The biodegradation rates (%) of |i=1,2,3,...,n} are respectively expressed as and The relative biodegradability of the plastic is further obtained according to equation 5:
[0038]
[0039] (2) performing data processing and graphing of the relative biodegradability of the plastic,
[0040] Among them, the logarithmic operation is used to convert the Convert to And plot y 3 The scatter plot relative to t is denoted as P 3 ={(y 3i ,t i)|i=1,2,3,...,n}, where {a 3 >0∩a 3 ≠1|a 3 ∈R}, that is, a 3 >0 and not equal to 1, and Right now
[0041] (3) For the scatter plot P in step (2) 3 Perform linear fitting and linear extrapolation.
[0042] Among them, the scatter plot P 3 Divide the data into at least two segments that are basically linearly related and contain as many continuous data points as possible, perform linear fitting on the data points of each segment, and record the data point of the segment with the largest slope of the linear fitting as P 3A , and its linear fitting equation is expressed as Equation 6:
[0043] Y 3A =k 3A t+c 3A Equation 6
[0044] P 3A The data point of the segment with the smallest slope of the linear fit on the left is recorded as P 3B , and its linear fitting equation is expressed as Equation 7:
[0045] Y 3B =k 3B t+c 3B Equation 7
[0046] where k 3A >0, and k 3A >k 3B ,
[0047] And wherein, the straight lines described by equation 6 and equation 7 are linearly extrapolated to obtain their intersection, and the time t corresponding to the intersection is obtained. c3 ;and
[0048] (4) Output analysis results,
[0049] The result includes the parameter t obtained in step (3) c3 , optionally also including k 3j and / or k 3B .
[0050] According to a fourth aspect of the present invention, there is provided a method for analyzing and evaluating the anti-degradation performance of plastics based on the linear extrapolation method of the aerobic biodegradation test results under controlled composting conditions, characterized in that the method comprises the following steps:
[0051] (1) conducting aerobic biodegradation tests on plastics under controlled composting conditions and obtaining the results of said tests,
[0052] Wherein, the plastic and the reference material are i The biodegradation rates (%) of |i=1,2,3,...,n} are respectively expressed as and The relative biodegradability of the plastic is further obtained according to equation 5:
[0053]
[0054] (2) performing data processing and graphing of the biodegradability of the plastic,
[0055] Among them, the logarithmic operation is used to convert the obtained value in step (1) into Convert to And convert time t into And plot y 4 Relative to x 2 The scatter plot is denoted as P 4 ={(y 4i ,x 2i )|i=1,2,3,...,n}, where {a 4 >0∩a 4 ≠1|a 4 ∈R}, that is, a 4 >0 and not equal to 1, and Right now
[0056] (3) For the scatter plot P in step (2) 4 Perform linear fitting and linear extrapolation.
[0057] Among them, the scatter plot P 4 Divide the data into at least two segments that are basically linearly related and contain as many continuous data points as possible, perform linear fitting on the data points of each segment, and record the data point of the segment with the largest slope of the linear fitting as P 4a , and its linear fitting equation is expressed as Equation 8:
[0058] Y 4A =k 4A x 2 +c 4A Equation 8
[0059] P 4A The data point of the segment with the smallest slope of the linear fit on the left is recorded as P 4B , and its linear fitting equation is expressed as Equation 9:
[0060] Y 4B =k 4B x 2 +c 4B Equation 9
[0061] where k 4A >0, and k 4A >k 4B ,
[0062] And wherein, the straight lines described by equation 8 and equation 9 are linearly extrapolated to obtain their intersection point, and the x corresponding to the intersection point is obtained. c4 , and by the equation Obtain the time t corresponding to the intersection point c4 ;and
[0063] (4) Output analysis results,
[0064] The result includes the parameter t obtained in step (3) c4 , optionally also including k 4A and / or k 4B .
[0065] According to a fifth aspect of the present invention, there is provided a system for evaluating the degradation resistance of plastics, characterized in that the system adopts the method according to any of the aforementioned aspects.
[0066] According to a sixth aspect of the present invention, there is provided a computer device, characterized in that it comprises:
[0067] Processor; and
[0068] A memory for storing executable instructions;
[0069] The processor is used to read and execute the executable instructions from the memory to implement the method described above.
[0070] According to a seventh aspect of the present invention, there is provided a computer-readable storage medium, characterized in that it stores a computer program, and when the computer program is executed by a processor, the method described above is implemented. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 It is the scatter plot and analysis results of Example 1.
[0072] Figure 2 It is the scatter plot and analysis results of Example 2.
[0073] Figure 3 It is the scatter plot and analysis results of Example 3.
[0074] Figure 4 It is the scatter plot and analysis results of Example 4. DETAILED DESCRIPTION
[0075] The present invention is described in more detail in the following paragraphs. Unless explicitly stated otherwise, each aspect described can be combined with any other one or more aspects. In particular, any feature indicated as being preferred can be combined with any other one or more features indicated as being preferred.
[0076] The recitation of numerical endpoints includes all numbers and fractions within the corresponding range, as well as the recited endpoints. It should be noted that when specifying any range of numerical values, any particular upper value can be associated with any particular lower value.
[0077] All references cited in this specification are incorporated herein by reference in their entirety.
[0078] In the context of the present invention, unless otherwise defined, all terms used in the present invention, including technical and scientific terms, have the meanings commonly understood by one of ordinary skill in the art to which the present invention belongs.
[0079] As used herein, the terms "comprising" and "consisting of" are synonymous with "including" or "containing" and are inclusive or open-ended and do not exclude additional, unrecited ingredients, components or process steps.
[0080] The term "degradation" or "decomposition" as used herein refers to the loss of certain properties caused by significant changes in the chemical structure of plastics under specific environmental conditions. It can be any process that can lead to a decrease in the molecular weight of a macromolecule or the conversion of a long-chain structure into a shorter-chain low-molecular substance. Depending on the process that occurs, there are three main possible degradation modes for plastic degradation, namely biological degradation, chemical degradation and physicochemical degradation.
[0081] The term "biodegradation" as used herein refers to the process by which plastics, as a source of nutrition for microbial life activities, are digested and absorbed by organisms such as bacteria, fungi and certain algae, transformed into simpler compounds, and ultimately into small molecules such as methane, carbon dioxide, and water. For example, the degradation of biodegradable plastics relies on biological processes that use the carbon-containing substances present in the plastics as a source of nutrition for microorganisms.
[0082] The term "chemical degradation" as used herein refers to the process in which plastics are degraded by oxidative degradation, photodegradation or hydrolysis, including oxidative degradation of plastics, photodegradable plastics, hydrolytic degradation of plastics, etc. In particular, the chemical degradation of the present invention refers to the degradation process before plastics can be digested and absorbed by organisms. As known to those skilled in the art, the aerobic biodegradation test under controlled composting conditions of the present invention is carried out under specified temperature, oxygen concentration, humidity and dark or weak light conditions, so the chemical degradation involved is mainly hydrolytic degradation.
[0083] The term "physical and chemical degradation" as used herein refers to the process in which plastics are degraded under the action of physical fields such as thermal fields, electric fields, and stress fields. In particular, the physicochemical degradation of the present invention refers to the degradation process before plastics can be digested and absorbed by organisms. As known to those skilled in the art, the aerobic biodegradation test under controlled composting conditions of the present invention is carried out under dark or weak light conditions, so the physicochemical degradation effect involved therein is relatively weak.
[0084] It is known in the art that the degradation rate of plastics is affected by many factors, including environmental factors such as temperature, humidity, pH, chemical media, light irradiation, etc., and factors of the plastic itself such as the primary structure, secondary structure, tertiary structure, molecular weight and its distribution, as well as composition, interface structure, physical form, porosity, impurities, etc. of the polymer. One object of the present invention is to reflect the comprehensive anti-degradation performance of plastics through the method of the present invention.
[0085] The term "aerobic biodegradation test under controlled composting conditions" as used herein refers to the determination of the final aerobic biodegradability and disintegration degree of plastic materials by measuring the amount of carbon dioxide emitted by plastic materials as organic compounds under controlled composting conditions according to methods known in the art. By observing the trend of its biodegradability or relative biodegradability over time, it can be found that there is a zero decomposition rate or even a negative decomposition rate in the initial stage of degradation, which is called the "hysteresis stage". Related studies have found (Handbook of Biodegradable Polymer, Edited by Abraham J.Domb, Joseph Kost and David M.Wiseman, published in 1997 by CRC Press, pages 451-453) that in the hysteresis stage, plastics can produce chemical structural changes before biodegradation through chemical degradation (such as hydrolysis, oxidative degradation, photodegradation, etc.) involving non-microorganisms under the action of factors such as water, temperature, pH, and chemical substances. For example, before aerobic biodegradation begins, polylactic acid first needs to break ester bonds and reduce molecular weight through hydrolysis (Hamad, Kotiba, et al. Properties and medical applications of polylactic acid: A review. Express polymer letters, 2015, 9 (5): 435-455). When the molecular weight is as low as a certain threshold, such as less than 10 kDa, its oligomers or monomers are water-soluble and can be digested and absorbed by microorganisms or cells (Lunt, J. Large-scale production, properties and commercial applications of polylactic acid polymers. Polymer Degradation and Stability, 1998, 59: 145-152). In the biochemical process involving aerobic microorganisms, its oligomers or monomers can be further decomposed into small molecules until they are finally decomposed into carbon dioxide and water.
[0086] As is known in the art, in an aerobic biodegradation test under controlled composting conditions, the cumulative production of carbon dioxide gas released is calculated by continuously monitoring and periodically measuring the production of carbon dioxide in the test container and the blank container. The ratio of the actual amount of carbon dioxide gas released by the plastic test material in the test to the theoretical amount of carbon dioxide that the material can produce is the biodegradation rate. It is known to those skilled in the art that the aerobic biodegradability test of plastic test materials under controlled composting conditions can be carried out according to the test procedures in the following standards: GB / T 19277.1 "Determination of the ultimate aerobic biodegradability of plastic materials under controlled composting conditions—Method by analysis of evolved carbon dioxide—Part 1: General method", or GB / T 19277.2 "Determination of the ultimate aerobic biodegradability of plastic materials under controlled composting conditions—Method by analysis of evolved carbon dioxide—Part 2: Gravimetric measurement of carbon dioxide evolved in a laboratory-scale test", or ISO 14855-1, or ISO 14855-2, or ASTM D5929 "Standard Test Method for Determining Biodegradability of Materials Exposed to Source-Separated Organic Municipal Solid Waste Mesophilic Composting Conditions by Respirometryor ASTM D5338 “Standard Test Method for Determining Aerobic Biodegradation of Plastic Materials Under Controlled Composting Conditions, Incorporating Thermophilic Temperatures”, or EN ISO 14855-1, or EN ISO 14855-2, or BS EN ISO 14855-1, or BS EN ISO 14855-2, or DIN EN ISO 14855-1, or DIN EN ISO 14855-2, or KS T ISO 20200 “Plastics-Determination of the degree of disintegration of plastic materials under simulated composting conditions in a laboratory-scale test”, or UNE-EN 14995 “Plastics-Evaluation of compostability-Test scheme andspecifications” (Test plans and specifications for the assessment of the compostability of plastics), or AS5810 “Biodegradable plastics—Biodegradable plastics suitable for home composting” (Biodegradable plastics—Biodegradable plastics suitable for home composting).
[0087] The "biodegradation rate" used in the present invention can be determined according to methods known in the art. For example, the biodegradation rate of the plastic test material can be calculated according to the following equation in GB / T 19277.1:
[0088]
[0089] Among them (CO 2 ) T is the cumulative amount of carbon dioxide released from the compost container containing the test material, (CO 2 ) B is the average value of the cumulative carbon dioxide released from the blank container, ThCO 2is the theoretical release of carbon dioxide produced by the test material. The same equation applies to the biodegradation rate of the reference material.
[0090] The aerobic biodegradation test under controlled composting conditions of the present invention can be carried out in a container or room, in darkness or weak light, without any steam that may affect the growth of microorganisms.
[0091] The "relative biodegradability" used in the present invention can be determined according to methods known in the art. For example, the relative biodegradability of the plastic test material can be further obtained according to the following equation:
[0092]
[0093] in, and are the plastic and the reference material at each time point {t i |i=1,2,3,...,n} biodegradation rate (%).
[0094] The term "digestion container / compost container" used herein refers to a container known in the art for aerobic biodegradation tests under controlled composting conditions. The digestion container can usually have a tightly connected glass container or a vessel made of other materials that does not affect the composting effect to avoid gas loss. The container may include a container with test materials, a container with reference materials or a blank container. The container can be connected to an air system and a carbon dioxide measurement system.
[0095] The term "plastic" as used herein refers to all types of plastics generally known in the art, in particular plastics that can be used for aerobic biodegradation tests under controlled composting conditions, such as plastics that can be subjected to aerobic biodegradation tests under controlled composting conditions according to the above 15 standards. The plastics may include, but are not limited to, all polymer compounds containing chemical bonds such as ester bonds, anhydride bonds (-RCOOOC-), orthoester bonds (-OCOR'R"OR-, ortho ester bonds), carbonate bonds (-ROCOO-), phosphate bonds (-OPOR'OOR-), ketal bonds (-OCR'R"OR-), acetal bonds (-OCHR'OR-), imino-carbonate bonds (-ROCNHO-), peptide bonds / amide bonds (-CONH-), and / or phosphazene bonds (-RR'P=N-), etc. on the main chain or branched chain skeleton structure.
[0096] The term "critical point" or "critical transition time point" as used herein refers to the critical state of transition from a chemical degradation process (such as hydrolytic degradation, oxidative degradation, etc.) involving no microorganisms to a biochemical process (biodegradation stage) involving microorganisms. The critical point is defined in the present invention as the t c .
[0097] The term "substantially linear relationship" as used herein means that a set of data points are substantially arranged in a straight line in a scatter plot. Specifically, the residual sum of squares (RSS) obtained by linear fitting of a set of data points that are substantially linear should be <0.05, or <0.025, or <0.01, or <0.001. As known to those skilled in the art, the linear relationship between two variables in a scatter plot includes positive correlation and negative correlation.
[0098] The validity of the results of the aerobic biodegradation test under controlled composting conditions obtained in step (1) of the method of the present invention can be evaluated according to methods known in the art, for example, according to the methods required in standards GB / T 19277.1 or GB / T 19277.2.
[0099] The plastic test material used in the present invention may have a form known in the art for aerobic biodegradation tests under controlled composting conditions, and may be added in a solid form, generally including a film, granules, powder, or a simple shape (e.g., dumbbell shape), etc., preferably in the form of granules or powder, more preferably in the form of granules, such as plastic masterbatch. Generally, the maximum surface area of each piece of plastic test material should not exceed 4 cm 2 , wherein if the size of the test material original exceeds the above maximum surface area, its size can be reduced to meet the requirements. For example, the test material can be in the form of particles with a diameter of about 1 cm or less, such as particles with a diameter of less than about 9 mm, less than about 8 mm, less than about 7 mm, less than about 6 mm, less than about 5 mm, less than about 4 mm, less than about 3 mm, less than about 2 mm or less.
[0100] According to the method of the first aspect of the present invention, the aerobic biodegradation test in step (1) can be carried out under the conditions of constant temperature and darkness or weak light, and the constant temperature can be at least 45°C, at least 46°C, at least 47°C, at least 48°C, at least 49°C, at least 50°C, at least 51°C, at least 52°C, at least 53°C, at least 54°C, at least 55°C, at least 56°C, at least 57°C, at least 58°C, at least 59°C, at least 60°C or higher. Preferably, the aerobic biodegradation test can be carried out under the conditions of constant temperature of 58°C±2°C and darkness or weak light.
[0101] According to the method of the first aspect of the present invention, the time described in step (1) can be in minutes (m), hours (h), or days (d). In some preferred embodiments, the time is in days (d).
[0102] According to the method of the first aspect of the present invention, t in equation 2 may be at least 1, at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, or at least 8 days. In some preferred embodiments, t may be at least 4 days, preferably at least 5 days, more preferably at least 6 days, particularly preferably at least 7 days, and most preferably at least 8 days.
[0103] According to the method of the first aspect of the present invention, the segments divided in step (3) may contain at least 5 consecutive data points, preferably at least 6, more preferably at least 7, and even more preferably at least 8, still more preferably at least 9, still more preferably at least 10, still more preferably at least 15, and still more preferably at least 20 consecutive data points.
[0104] According to the method of the first aspect of the present invention, the base of the logarithmic operation in step (2) should satisfy {a 1 >0∩a 1 ≠1|a 1 ∈R}, that is, a 1 >0 and not equal to 1, for example, a 1 >1, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10 or more, typically 10 or the natural constant e.
[0105] According to the method of the first aspect of the present invention, the parameter b in step (2) 1 Should meet Right now In some embodiments, parameter b 1 Can meet 0% 1 <100%, or 0% 1 <90%, or 1% 1 <60%, or 2% 1 <40%, or 5% 1 <20%, or b 1 =1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95%.
[0106] In some embodiments of the present invention, the biodegradation rate is obtained in step (1) of the method of the first aspect. The maximum value may be less than 10%, less than 9%, less than 8%, less than 7%, less than 10%, less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, less than 4.5%, less than 4%, less than 3.5%, less than 3%, less than 2.5%, less than 2%, or less than 1.5%.
[0107] In some embodiments of the present invention, the biodegradation rate is obtained in step (1) of the method of the first aspect. The maximum value may be at least 1%, at least 1.5%, at least 2%, at least 2.5%, at least 3%, at least 3.5%, at least 4%, at least 4.5%, at least 5%, at least 6%, at least 7%, at least 8%, at least 9%, or at least 10%.
[0108] In some embodiments of the present invention, the time t in step (1) of the method of the first aspect is n It may be at least 48 hours, at least 3, at least 4, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 45, at least 60 or at least 90 days.
[0109] According to the method of the second aspect of the present invention, the aerobic biodegradation test in step (1) can be carried out under the conditions of constant high temperature and darkness or weak light, and the constant high temperature can be at least 45°C, at least 46°C, at least 47°C, at least 48°C, at least 49°C, at least 50°C, at least 51°C, at least 52°C, at least 53°C, at least 54°C, at least 55°C, at least 56°C, at least 57°C, at least 58°C, at least 59°C, at least 60°C or higher. Preferably, the aerobic biodegradation test can be carried out under the conditions of constant temperature of 58°C±2°C and darkness or weak light.
[0110] According to the method of the second aspect of the present invention, the time in step (1) can be in hours (h) or days (d). In some preferred embodiments, the time is in days (d).
[0111] According to the method of the second aspect of the present invention, x in equation 4 1 The corresponding t can be at least 1, at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, or at least 8 days. In some preferred embodiments, the t can be at least 4 days, preferably at least 5 days, more preferably at least 6 days, particularly preferably at least 7 days, and most preferably at least 8 days.
[0112] According to the method of the second aspect of the present invention, the segments divided in step (3) may contain at least 5 consecutive data points, preferably at least 6, more preferably at least 7, and even more preferably at least 8, still more preferably at least 9, still more preferably at least 10, still more preferably at least 15, and still more preferably at least 20 consecutive data points.
[0113] According to the method of the second aspect of the present invention, the base of the logarithmic operation in step (2) should satisfy {a 2 >0∩a 2 ≠1|a 2 ∈R}, that is, a 2 >0 and not equal to 1, for example, a 2 >1, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10 or more, typically 10 or the natural constant e.
[0114] According to the method of the second aspect of the present invention, the parameter b in step (2) 2 Should meet Right now In some embodiments, parameter b 2 Can meet 0% 2 <100%, or 0% 2 <90%, or 1% 2 <60%, or 2% 2 <40%, or 5% 2 <20%, or b 2 =1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95%.
[0115] In some embodiments of the present invention, the biodegradation rate is obtained in step (1) of the method of the second aspect. The maximum value may be less than 10%, less than 9%, less than 8%, less than 7%, less than 10%, less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, less than 4.5%, less than 4%, less than 3.5%, less than 3%, less than 2.5%, less than 2%, or less than 1.5%.
[0116] In some embodiments of the present invention, the biodegradation rate is obtained in step (1) of the method of the second aspect. The maximum value may be at least 1%, at least 1.5%, at least 2%, at least 2.5%, at least 3%, at least 3.5%, at least 4%, at least 4.5%, at least 5%, at least 6%, at least 7%, at least 8%, at least 9%, or at least 10%.
[0117] In some embodiments of the present invention, the time t in step (1) of the method of the second aspect is n It may be at least 48 hours, at least 3, at least 4, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 45, at least 60 or at least 90 days.
[0118] According to the method of the third aspect of the present invention, the aerobic biodegradation test in step (1) can be carried out under the conditions of constant high temperature and darkness or weak light, and the constant high temperature can be at least 45°C, at least 46°C, at least 47°C, at least 48°C, at least 49°C, at least 50°C, at least 51°C, at least 52°C, at least 53°C, at least 54°C, at least 55°C, at least 56°C, at least 57°C, at least 58°C, at least 59°C, at least 60°C or higher. Preferably, the aerobic biodegradation test can be carried out under the conditions of constant temperature of 58°C±2°C and darkness or weak light.
[0119] According to the method of the third aspect of the present invention, the reference material in step (1) can be any reference material known in the art for aerobic biodegradation tests, for example, cellulose. In some embodiments of the present invention, the reference material can be α-cellulose powder with a particle size of less than 25 μm.
[0120] According to the method of the third aspect of the present invention, the time in step (1) can be in hours (h) or days (d). In some preferred embodiments, the time is in days (d).
[0121] According to the method of the third aspect of the present invention, t in equation 7 may be at least 1, at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, or at least 8 days. In some preferred embodiments, t may be at least 4 days, preferably at least 5 days, more preferably at least 6 days, particularly preferably at least 7 days, and most preferably at least 8 days.
[0122] According to the method of the third aspect of the present invention, the segments divided in step (3) may include at least 5 consecutive data points, preferably at least 6, more preferably at least 7, and even more preferably at least 8, still more preferably at least 9, still more preferably at least 10, still more preferably at least 15, and still more preferably at least 20 consecutive data points.
[0123] According to the method of the third aspect of the present invention, the base of the logarithmic operation in step (2) should satisfy {a 3 >0∩a 3 ≠1|a 3 ∈R}, that is, a 3 >0 and not equal to 1, for example, a 3 >1, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10 or more, typically 10 or the natural constant e.
[0124] According to the method of the third aspect of the present invention, the parameter b in step (2) 3 Should meet Right now In some embodiments, parameter b 3 Can meet 0% 3 <100%, or 0% 3 <90%, or 1% 3 <60%, or 2% 3 <40%, or 5% 3 <20%, or b 3 =1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95%.
[0125] In some embodiments of the present invention, the relative biodegradability is obtained in step (1) of the method of the third aspect. The maximum value may be less than 10%, less than 9%, less than 8%, less than 7%, less than 10%, less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, less than 4.5%, less than 4%, less than 3.5%, less than 3%, less than 2.5%, less than 2%, or less than 1.5%.
[0126] In some embodiments of the present invention, the relative biodegradability is obtained in step (1) of the method of the third aspect. The maximum value may be at least 1%, at least 1.5%, at least 2%, at least 2.5%, at least 3%, at least 3.5%, at least 4%, at least 4.5%, at least 5%, at least 6%, at least 7%, at least 8%, at least 9%, or at least 10%.
[0127] In some embodiments of the present invention, the time t in step (1) of the method of the third aspect is n It may be at least 48 hours, at least 3, at least 4, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 45, at least 60 or at least 90 days.
[0128] According to the method of the fourth aspect of the present invention, the aerobic biodegradation test in step (1) can be carried out under the conditions of constant high temperature and darkness or weak light, and the constant high temperature can be at least 45°C, at least 46°C, at least 47°C, at least 48°C, at least 49°C, at least 50°C, at least 51°C, at least 52°C, at least 53°C, at least 54°C, at least 55°C, at least 56°C, at least 57°C, at least 58°C, at least 59°C, at least 60°C or higher. Preferably, the aerobic biodegradation test can be carried out under the conditions of constant temperature of 58°C±2°C and darkness or weak light.
[0129] According to the method of the fourth aspect of the present invention, the reference material in step (1) can be any reference material known in the art for aerobic biodegradation tests, for example, cellulose. In some embodiments of the present invention, the reference material can be α-cellulose powder with a particle size of less than 25 μm.
[0130] According to the method of the fourth aspect of the present invention, the time in step (1) can be in hours (h) or days (d). In some preferred embodiments, the time is in days (d).
[0131] According to the method of the fourth aspect of the present invention, x in equation 9 2 The corresponding t can be at least 1, at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, or at least 8 days. In some preferred embodiments, the t can be at least 4 days, preferably at least 5 days, more preferably at least 6 days, particularly preferably at least 7 days, and most preferably at least 8 days.
[0132] According to the method of the fourth aspect of the present invention, the segments divided in step (3) may include at least 5 consecutive data points, preferably at least 6, more preferably at least 7, even more preferably at least 8, still more preferably at least 9, still more preferably at least 10, still more preferably at least 15, still more preferably at least 20 consecutive data points.
[0133] According to the method of the fourth aspect of the present invention, the base of the logarithmic operation in step (2) should satisfy {a 4 >0∩a 4 ≠1|a 4 ∈R}, that is, a 4 >0 and not equal to 1, for example, a 4>1, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10 or more, typically 10 or the natural constant e.
[0134] According to the method of the fourth aspect of the present invention, the parameter b in step (2) 4 Should meet Right now In some embodiments, parameter b 4 Can meet 0% 4 <100%, or 0% 4 <90%, or 1% 4 <60%, or 2% 4 <40%, or 5% 4 <20%, or b 4 =1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95%.
[0135] In some embodiments of the present invention, the relative biodegradability is obtained in step (1) of the method of the fourth aspect. The maximum value may be less than 10%, less than 9%, less than 8%, less than 7%, less than 10%, less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, less than 4.5%, less than 4%, less than 3.5%, less than 3%, less than 2.5%, less than 2%, or less than 1.5%.
[0136] In some embodiments of the present invention, the relative biodegradability is obtained in step (1) of the method of the fourth aspect. The maximum value may be at least 1%, at least 1.5%, at least 2%, at least 2.5%, at least 3%, at least 3.5%, at least 4%, at least 4.5%, at least 5%, at least 6%, at least 7%, at least 8%, at least 9%, or at least 10%.
[0137] In some embodiments of the present invention, the time t in step (1) of the method of the fourth aspect is n It may be at least 48 hours, at least 3, at least 4, at least 5, at least 10, at least 15, at least 20, at least 25, at least 30, at least 35, at least 45, at least 60 or at least 90 days.
[0138] Example
[0139] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
[0140] The materials and test instruments used in the aerobic biodegradation tests in Examples 1 to 4 are shown below:
[0141] -Testing instrument: Bioprocess Control Gas Endeavour biodegradation test system produced by Bioprocess Control Sweden AB;
[0142] -Plastics: All are polyester plastics, specifically poly (L-lactic acid) resin (PLA, CAS: 26100-51-6, molecular formula (C 3 H 4 O 2 ) n ), the dosage is 7.5g, in the form of particles with a diameter of about 3mm, wherein the melting point of poly (L-lactic acid) resin 1# is 160.0℃, the melt index is 17.1g / 10min (190℃, 2.16kg), the molecular weight distribution index is 1.65, the glass transition temperature (T g ) is 58.7°C and the density is 1.25g / cm 3 , lactide content is 0.33%, the melting point of poly (L-lactic acid) resin 2# is 174.6℃, the melt index is 4.9g / 10min (190℃, 2.16kg), the molecular weight distribution index is 1.58, and the glass transition temperature (T g ) is 59.9°C and the density is 1.25g / cm 3 , lactide content is 0.11%, the melting point of poly (L-lactic acid) resin 3# is 177.3℃, the melt index is 4.6g / 10min (190℃, 2.16kg), the molecular weight distribution index is 1.62, and the glass transition temperature (T g ) is 60.8℃ and the density is 1.25g / cm 3 , lactide content is 0.20%, the performance index test method of the above poly (L-lactic acid) resin is carried out in accordance with the national standard GB / T 29284-2024 "Polylactic Acid"; the modified polylactic acid resin, the amount is 7.5g, in the form of particles with a diameter of about 3mm, including 181 type modified polylactic acid resin.
[0143] -Inoculum: All were aerobic compost from Bipu Instrument (Zhejiang) Co., Ltd., and the dosage was 500g;
[0144] - Reference material: cellulose powder from Shanghai Aladdin Biochemical Technology Co., Ltd. (α-cellulose powder, CAS: 9004-34-6, particle size ≤ 25 μm);
[0145] -Digestion vessel: 1L Schott blue cap glass reagent bottle.
[0146] Example 1
[0147] According to GB / T 19277.1 "Determination of the ultimate aerobic biodegradability of materials under controlled composting conditions - Method for determination of released carbon dioxide - Part 1: General method", poly (L-lactic acid) resin 1# was tested for aerobic biodegradability under controlled composting conditions, with α-cellulose powder as the reference material, and the test was conducted under weak light conditions at a temperature of 58℃±2℃. The cumulative carbon dioxide gas release in each digestion container was counted and recorded in units of days (d), and the biodegradation rate of the test material was calculated.
[0148] Through logarithmic operation, the above obtained Convert to where a 1 =10, b 1 = 1%, and plot y 1 The scatter plot relative to t is as follows Figure 1 As shown. Figure 1 It can be clearly observed from the scatter plot that the segment (i) corresponding to the continuous data points of 13 days ≤ t ≤ 18 days is basically linear, and compared with other segments, y in segment (i) 1 It has a more significant positive linear relationship with t, that is, the slope of its linear fit is larger. In addition, on the left side of the above segment (i), the segment (ii) corresponding to the continuous data points of 3 days ≤ t ≤ 9 days is also basically linear, and compared with other segments, y in segment (ii) is 1 It has a more significant negative correlation linear relationship with t, that is, the slope of its linear fitting is smaller. Linear fitting is performed on the data points of the above two segments respectively, and the corresponding linear equation Y is obtained 1A =0.06137t-2.05894, and the residual sum of squares is 7.99182×10 -4 , and Y 1B =-0.00083t-1.43625, and the residual sum of squares is 0.00188. The intersection of the two straight lines is obtained by linear extrapolation, and the critical point time t is obtained. c1 =10.02d, the slope of the linear region on the left side of the critical point is k1B =-0.00083d -1 , the slope k of the linear region to the right of the critical point 1A =0.06137d -1 .
[0149] Example 2
[0150] According to ISO 14855-1 “Determination of the ultimate aerobic biodegradability of plastic materials under controlled composting conditions-Method by analysis of evolved carbon dioxide-Part 1: General method”, poly (L-lactic acid) resin 2# was subjected to aerobic biodegradation test, with α-cellulose powder as reference material, and the test was conducted under weak light conditions at a temperature of 58℃±2℃. The cumulative carbon dioxide gas release in each digestion container was counted and recorded in units of days (d), and the biodegradation rate of the test material was calculated.
[0151] Through logarithmic operation, the above obtained and time t are transformed into and where a 2 =e(natural constant), b 2 = 10%, and plot y 2 Relative to x 1 A scatter plot of Figure 2 As shown. Figure 2 The scatter plot clearly shows that 3.13549≤x 1 The segment (i) of consecutive data points with t≤3.82864 (i.e., 22 days≤t≤45 days) is basically linear, and compared with other segments, y in segment (i) is 2 With x 1 It has a more significant positive linear relationship, that is, the slope of its linear fit is larger. In addition, on the left side of the above segment (i), corresponding to 2.19722≤x 1 The segment (ii) of the continuous data points with t≤2.89037 (i.e., 8 days≤t≤17 days) is also substantially linear, and compared with other segments, y in segment (ii) is 2 With x 1 It has a more significant negative correlation linear relationship, that is, the slope of its linear fitting is smaller. Linear fitting is performed on the data points of the above two segments respectively, and the corresponding linear equation Y is obtained.2A =1.30844x 1 -7.18075, its residual sum of squares is 0.03784, and Y 2B =-0.93412x 1 -0.43712, and the residual sum of squares is 0.00218. Through linear extrapolation, we can get the intersection of the two straight lines and obtain x c2 =3.0089, that is, the critical point time t c2 =19.27d, the slope of the linear region on the left side of the critical point is k 2B =-0.93412d -1 , the slope k of the linear region to the right of the critical point 2A =1.30844d -1 .
[0152] Example 3
[0153] According to EN ISO 14855-1 “Determination of the ultimate aerobic biodegradability of plastic materials under controlled composting conditions-Method by analysis of evolved carbon dioxide-Part 1: General method”, poly (L-lactic acid) resin 3# was subjected to aerobic biodegradation test, with α-cellulose powder as reference material, and the test was carried out under weak light conditions at a temperature of 58℃±2℃. The cumulative carbon dioxide gas release in each digestion container was counted and recorded in units of days (d), and the biodegradation rate of the test material was calculated. and relative biodegradability
[0154] Through logarithmic operation, the above obtained Convert to where a 3 =e(natural constant), b 3 = 10%, and plot y 3 The scatter plot relative to t is as follows Figure 3 As shown. Figure 3 It can be clearly observed from the scatter plot that the segment (i) corresponding to the continuous data points of 28 days ≤ t ≤ 41 days is basically linear, and compared with other segments, y in segment (i) 3It has a more significant positive linear relationship with t, that is, the slope of its linear fit is larger. In addition, on the left side of the above segment (i), the segment (ii) corresponding to the continuous data points of 8 days ≤ t ≤ 16 days is also basically linear, and compared with other segments that can be linearly fitted, y in segment (ii) is 3 It has a more significant negative correlation linear relationship with t, that is, the slope of its linear fitting is smaller. Linear fitting is performed on the data points of the above two segments respectively, and the corresponding linear equation Y is obtained 3A =0.05758t-4.56372, the residual sum of squares is 0.03572, and Y 3B =-0.05612t-2.17358, and the residual sum of squares is 0.02663. The intersection of the two straight lines is obtained by linear extrapolation, and the critical point time t is obtained. c3 =21.02d, the slope of the linear region on the left side of the critical point is k 3B =-0.05612d -1 , the slope k of the linear region to the right of the critical point 3A =0.05758d -1 .
[0155] Example 4
[0156] According to DIN EN ISO 14855-1 “Determination of the ultimate aerobic biodegradability of plastic materials under controlled composting conditions-Method by analysis of evolved carbon dioxide-Part 1: General method”, the samples from Zhejiang Hisun Biomaterials Co., Ltd. were analyzed. The 181 type modified polylactic acid resin was subjected to an aerobic biodegradation test, with α-cellulose powder as the reference material, and the test was conducted under weak light conditions at a temperature of 58°C±2°C. The cumulative carbon dioxide gas release in each digestion container was counted and recorded in units of days (d), and the biodegradation rate of the test material was calculated. and relative biodegradability
[0157] Through logarithmic operation, the above obtained Convert to and where a 4 =10, b 2 = 15%, and plot y 4 Relative to x 2A scatter plot of Figure 4 As shown. Figure 4 The scatter plot clearly shows that the corresponding value is 1.25527≤x 2 The segment (i) of consecutive data points with t≤1.59106 (i.e., 17 days≤t≤38 days) is basically linear, and compared with other segments, y in segment (i) is 4 With x 2 It has a more significant positive linear relationship, that is, the slope of its linear fit is larger. In addition, on the left side of the above segment (i), corresponding to 0.8451≤x 2 The segment (ii) of the continuous data points with t≤1.25527 (i.e., 6 days≤t≤17 days) is also basically linearly related, and compared with other segments that can be linearly fitted, y in segment (ii) is 4 With x 2 The linear relationship with a more significant negative correlation is that the slope of its linear fitting is smaller. Linear fitting is performed on the data points of the above two segments respectively, and the corresponding linear equation Y is obtained. 4A =1.55824x 2 -3.12165, its residual sum of squares is 0.01192, and T 4B =-0.65664x 2 -0.36744, and the residual sum of squares is 0.0037. Through linear extrapolation, we can get the intersection of the two straight lines and obtain x c4 =1.2439, that is, the critical point time t c4 =16.53d, the slope of the linear region on the left side of the critical point is k 4B =-0.65664d -1 , the slope k of the linear region to the right of the critical point 4A =1.55824d -1 .
[0158] As can be seen from Examples 1 to 4, when processing the initial data of a complex aerobic biodegradation test of plastics, the method of the present invention can simply transform the "rough" raw data reflecting the initial aerobic degradation characteristics of the degradable plastic into an accurate mathematical equation through the operation of linear fitting, and the output result reflecting the corresponding degradation characteristics of the degradable plastic is clearly defined and calculated through the mathematical equation. It is believed that t c The larger the value, the better the plastic's resistance to chemical degradation.
Claims
1. A method for analyzing and evaluating the anti-degradation performance of plastics based on the linear extrapolation method of aerobic biodegradation test results under controlled composting conditions, characterized in that: The method includes the following steps: (1) Conduct an aerobic biodegradation test of the plastic under controlled composting conditions to obtain the results of the test. Wherein, the plastic is i The biodegradability (%) of |i=1,2,3,...,n} is recorded as (2) Process the data and draw a graph of the biodegradation rate of the plastic. Among them, the logarithmic operation is used to convert the obtained value in step (1) into Convert to And draw a scatter plot of y1 relative to t, and record the scatter plot as P1={(y 1i ,t i )|i=1,2,3,...,n}, where {a1>0∩a1≠1|a1∈R}, that is, a1>0 and not equal to 1, and Right now (3) Perform linear fitting and linear extrapolation on the scatter plot P1 in step (2). The scatter plot P1 is divided into at least two segments that are substantially linearly related and contain as many continuous data points as possible, and a linear fit is performed on the data points of each segment, and the data point of the segment with the largest slope of the linear fit is recorded as P 1A , and its linear fitting equation is expressed as Equation 1: Y 1A =k 1A t+c 1A Equation 1 P 1A The data point of the segment with the smallest slope of the linear fit on the left is recorded as P 1B , and its linear fitting equation is expressed as Equation 2: Y 1B =k 1B t+c 1B Equation 2 where k 1A >0, and k 1A >k 1B , And wherein, the straight lines described by equation 1 and equation 2 are linearly extrapolated to obtain the intersection point, and the time t corresponding to the intersection point is obtained. c1 ;and (4) Output the analysis results. The result includes the parameter t obtained in step (3) c1 , optionally also including k 1A and / or k 1B .
2. The method according to claim 1, characterized in that The aerobic biodegradation test in step (1) is carried out under the conditions of a constant temperature of 58°C ± 2°C and darkness or low light.
3. The method according to claim 1, characterized in that: The time in step (1) is in units of days (d).
4. The method according to claim 3, characterized in that In the equation 2, t is at least 4 days, preferably at least 5 days, more preferably at least 6 days, particularly preferably at least 7 days, most preferably at least 8 days.
5. The method according to claim 3 or 4, characterized in that: The section divided in step (3) contains at least 6 consecutive data points, preferably at least 7, more preferably at least 8, still more preferably at least 9, yet more preferably at least 10, particularly preferably at least 15 consecutive data points.
6. The method according to any one of claims 1 to 4, characterized in that: In step (2), the base a1 of the logarithmic operation is > 1, or is 10 or the natural constant e.
7. The method according to any one of claims 1 to 4, characterized in that: The parameter b1 in step (2) satisfies 0% < b1 < 100%, or 0% < b1 < 90%, or 1% < b1 < 60%, or 2% < b1 < 40%, or 5% < b1 < 20%, or b1 = 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95%.
8. A method for analyzing and evaluating the anti-degradation performance of plastics based on the linear extrapolation method of the results of aerobic biodegradation tests under controlled composting conditions, characterized in that: The method includes the following steps: (1) Conduct an aerobic biodegradation test of the plastic under controlled composting conditions to obtain the results of the test. Wherein, the plastic is i The biodegradability (%) of |i=1,2,3,...,n} is recorded as (2) Process the data and draw a graph of the biodegradation rate of the plastic. Among them, the logarithmic operation is used to convert the obtained value in step (1) into Convert to And convert time t into And draw a scatter plot of y2 relative to x1, and record the scatter plot as P2={(y 2i ,x 1i )|i=1,2,3,...,n}, where {a2>0∩a2≠1|a2∈R}, that is, a2>0 and not equal to 1, and Right now (3) Perform linear fitting and linear extrapolation on the scatter plot P2 in step (2). The scatter plot P2 is divided into at least two substantially linear segments containing as many continuous data points as possible, and a linear fit is performed on the data points of each segment, and the data point of the segment with the largest slope of the linear fit is recorded as P 2A , and its linear fitting equation is expressed as Equation 3: Y 2A =k 2A x1+c 2A Equation 3 P 2A The data point of the segment with the smallest slope of the linear fit on the left is recorded as P 2B , and its linear fitting equation is expressed as Equation 4: Y 2B =k 2B x1+c 2B Equation 4 where k 2A >0, and k 2A >k 2B , And wherein, the straight lines described by equation 3 and equation 4 are linearly extrapolated to obtain the intersection point, and the x corresponding to the intersection point is obtained. c2 , and by the equation Obtain the time t corresponding to the intersection point c2 ;and (4) Output the analysis results. The result includes the parameter t obtained in step (3) c2 , optionally also including k 2A and / or k 2B .
9. The method according to claim 8, characterized in that The aerobic biodegradation test in step (1) is carried out under the conditions of a constant temperature of 58°C ± 2°C and darkness or low light.
10. The method according to claim 8, characterized in that The time in step (1) is in units of days (d).
11. The method according to claim 10, characterized in that In the equation 4, the t corresponding to x1 is at least 4 days, preferably at least 5 days, more preferably at least 6 days, particularly preferably at least 7 days, most preferably at least 8 days.
12. The method according to claim 10 or 11, characterized in that: The section divided in step (3) contains at least 6 consecutive data points, preferably at least 7, more preferably at least 8, still more preferably at least 9, yet more preferably at least 10, particularly preferably at least 15 consecutive data points.
13. The method according to any one of claims 8 to 11, characterized in that In step (2), the base a2 of the logarithmic operation is > 1, or is 10 or the natural constant e.
14. The method according to any one of claims 8 to 11, characterized in that The parameter b2 in step (2) satisfies 0% < b2 < 100%, or 0% < b2 < 90%, or 1% < b2 < 60%, or 2% < b2 < 40%, or 5% < b2 < 20%, or b2 = 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95%.
15. A method for analyzing and evaluating the anti-degradation performance of plastics based on the linear extrapolation method of the results of aerobic biodegradation tests under controlled composting conditions, characterized in that: The method comprises the following steps: (1) Conduct an aerobic biodegradation test of the plastic under controlled composting conditions to obtain the results of the test, Wherein, the plastic and the reference material are i The biodegradation rates (%) of |i=1,2,3,...,n} are respectively expressed as and The relative biodegradability of the plastic is further obtained according to equation 5: (2) Process the data and plot the graph of the relative biodegradation rate of the plastic, Among them, the logarithmic operation is used to convert the Convert to And draw a scatter plot of y3 relative to t, and record the scatter plot as P3 = {(y 3i ,t i )|i=1,2,3,...,n}, where {a3>0∩a3≠1|a3∈R}, that is, a3>0 and not equal to 1, and Right now (3) Perform linear fitting and linear extrapolation on the scatter plot P3 in step (2), The scatter plot P3 is divided into at least two substantially linear segments containing as many continuous data points as possible, and a linear fit is performed on the data points of each segment, and the data point of the segment with the largest slope of the linear fit is recorded as P 3A , and its linear fitting equation is expressed as Equation 6: Y 3A =k 3A t+c 3A Equation 6 P 3A The data point of the segment with the smallest slope of the linear fit on the left is recorded as P 3B , and its linear fitting equation is expressed as Equation 7: Y 3B =k 3B t+c 3B Equation 7 where k 3A >0, and k 3A >k 3B , And wherein, the straight lines described by equation 6 and equation 7 are linearly extrapolated to obtain their intersection, and the time t corresponding to the intersection is obtained. c3 ;and (4) Output the analysis results, The result includes the parameter t obtained in step (3) c3 , optionally also including k 3A and / or k 3B .
16. The method according to claim 15, characterized in that The aerobic biodegradation test in step (1) is carried out under the conditions of a constant temperature of 58°C ± 2°C and darkness or low light.
17. The method according to claim 15, characterized in that The reference material in step (1) is α-cellulose powder with a particle size less than 25 μm.
18. The method according to claim 15, characterized in that The time in step (1) is in days (d).
19. The method according to claim 18, characterized in that The t in Equation 7 is at least 4 days, preferably at least 5 days, more preferably at least 6 days, particularly preferably at least 7 days, and most preferably at least 8 days.
20. The method according to claim 18 or 19, characterized in that The section divided in step (3) contains at least 6 consecutive data points, preferably at least 7, more preferably at least 8, still more preferably at least 9, yet more preferably at least 10, and particularly preferably at least 15 consecutive data points.
21. The method according to any one of claims 15 to 19, characterized in that The base a3 of the logarithmic operation in step (2) > 1, or is 10 or the natural constant e.
22. The method according to any one of claims 15 to 19, characterized in that The parameter b3 in step (2) satisfies 0% < b3 < 100%, or 0% < b3 < 90%, or 1% < b3 < 60%, or 2% < b3 < 40%, or 5% < b3 < 20%, or b3 = 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95%.
23. A method for analyzing and evaluating the anti-degradation performance of plastics based on the linear extrapolation method of the results of aerobic biodegradation tests under controlled composting conditions, characterized in that: The method comprises the following steps: (1) Conduct an aerobic biodegradation test of the plastic under controlled composting conditions to obtain the results of the test, Wherein, the plastic and the reference material are i The biodegradation rates (%) of |i=1,2,3,...,n} are respectively expressed as and The relative biodegradability of the plastic is further obtained according to equation 5: (2) Process the data and plot the graph of the biodegradation rate of the plastic, Among them, the logarithmic operation is used to convert the obtained value in step (1) into Convert to And convert time t into And draw a scatter plot of y4 relative to x2, and record the scatter plot as P4={(y 4i ,x 2i )|i=1,2,3,...,n}, where {a4>0∩a4≠1|a4∈R}, that is, a4>0 and not equal to 1, and Right now (3) Perform linear fitting and linear extrapolation on the scatter plot P4 in step (2), The scatter plot P4 is divided into at least two substantially linear segments containing as many continuous data points as possible, and a linear fit is performed on the data points of each segment, and the data point of the segment with the largest slope of the linear fit is recorded as P 4A , and its linear fitting equation is expressed as Equation 8: Y 4A =k 4A x2+c 4A Equation 8 P 4A The data point of the segment with the smallest slope of the linear fit on the left is recorded as P 4B , and its linear fitting equation is expressed as Equation 9: Y 4B =k 4B x2+c 4B Equation 9 where k 4A >0, and k 4A >k 4B , And wherein, the straight lines described by equation 8 and equation 9 are linearly extrapolated to obtain their intersection point, and the x corresponding to the intersection point is obtained. c4 , and by the equation Obtain the time t corresponding to the intersection point c4 ;and (4) Output the analysis results, The result includes the parameter t obtained in step (3) c4 , optionally also including k 4A and / or k 4B .
24. The method according to claim 23, characterized in that The aerobic biodegradation test in step (1) is carried out under the conditions of a constant temperature of 58°C ± 2°C and darkness or low light.
25. The method according to claim 23, characterized in that The reference material in step (1) is α-cellulose powder with a particle size less than 25 μm.
26. The method according to claim 23, characterized in that The time in step (1) is in days (d).
27. The method according to claim 26, characterized in that The t corresponding to x2 in Equation 9 is at least 4 days, preferably at least 5 days, more preferably at least 6 days, particularly preferably at least 7 days, and most preferably at least 8 days.
28. The method according to claim 26 or 27, characterized in that The section divided in step (3) contains at least 6 consecutive data points, preferably at least 7, more preferably at least 8, still more preferably at least 9, yet more preferably at least 10, and particularly preferably at least 15 consecutive data points.
29. The method according to any one of claims 23 to 27, characterized in that In step (2), the base a4 of the logarithmic operation is greater than 1, or is 10 or the natural constant e.
30. The method according to any one of claims 23 to 27, characterized in that In step (2), the parameter b4 satisfies 0% < b4 < 100%, or 0% < b4 < 90%, or 1% < b4 < 60%, or 2% < b4 < 40%, or 5% < b4 < 20%, or b4 = 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or 95%.
31. A system for evaluating the anti-degradation performance of plastics, characterized in that: The system adopts the method according to any one of the preceding claims.
32. A computer device, characterized in that: It includes: a processor; and a memory for storing executable instructions; wherein, the processor is configured to read and execute the executable instructions from the memory to implement the method according to any one of claims 1 to 30.
33. A computer-readable storage medium, characterized in that: It stores a computer program, which when executed by a processor, enables the implementation of the method according to any one of claims 1 to 30.
Citation Information
Patent Citations
A method for manufacturing a polymer article
CN108136642A
Biodegradable plant fiber plastic and preparation method thereof
CN112677278A
Device and method for testing biodegradability of biodegradable mulching film
CN112748239A
Method and system for obtaining scientific knowledge discovery
CN115841110A
Literature-based geoscience research hotspot extraction and visualization method and system
CN117708333A